A dwarf among giants: phylogenetic position of the elusive Angolan Adder (Bitis heraldica) and biogeographic affinities of Angolan Afromontane regions. Issue 1 (31st August 2020) - Ceríaco, Luis MP; Tolley, Krystal A; Marques, Mariana P; Heinicke, Matthew P; Bauer, Aaron M
ABSTRACT: The Angolan Adder, Bitis heraldica (Bocage, 1889), is endemic to the Angolan central plateau and is one of the most poorly known and rarely observed species of African snakes. The phylogenetic placement of B. heraldica within the four subgenera of the genus Bitis ( Bitis, Macrocerastes, Calechidna, Keniabitis ) has been problematic. The few recent taxonomic and phylogenetic revisions dealing with African viperids and the genus Bitis have not included this species, resulting in the default acceptance of B. heraldica as member of the subgenus Calechidna, based on similar morphology and size. During a survey in Huambo Province, central Angola, we collected the first specimen of this species in the past 65 years, allowing us to examine its phylogenetic relationships to other Bitis using multigene Bayesian and maximum likelihood analyses of all species of Bitis, except B. harenna . Contrary to expectations that B. heraldica is a member of the subgenus Calechidna, our results unambiguously place B. heraldica among members of the subgenus Macrocerastes, which contains the largest-bodied species of the genus. The placement of B. heraldica within Macrocerastes raises interesting questions about body-size evolution in viperids and contributes to a better understanding of biogeographic patterns in south-western Africa, and particularly Angola.